2015
DOI: 10.1021/acs.biochem.5b00977
|View full text |Cite
|
Sign up to set email alerts
|

Detection of RNA–Protein Interactions in Living Cells with SHAPE

Abstract: SHAPE-MaP is unique among RNA structure probing strategies in that it both measures flexibility at single-nucleotide resolution and quantifies the uncertainties in these measurements. We report a straightforward analytical framework that incorporates these uncertainties to enable detection of RNA structural differences between any two states, and we use it here to detect RNA-protein interactions in healthy mouse trophoblast stem cells. We validate this approach by analysis of three model cytoplasmic and nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
248
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(255 citation statements)
references
References 47 publications
3
248
0
Order By: Relevance
“…However, recent reports have suggested that 1M7, an isatoic anhydride reagent related to NMIA, was able to robustly modify both ribosomal RNA as well as mRNAs inside both mammalian and bacterial cells (McGinnis et al 2015;Smola et al 2015;Takahashi et al 2016;Watters et al 2016). These apparently contradictory results stimulated us to further investigate the differences between the two types of SHAPE reagents.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, recent reports have suggested that 1M7, an isatoic anhydride reagent related to NMIA, was able to robustly modify both ribosomal RNA as well as mRNAs inside both mammalian and bacterial cells (McGinnis et al 2015;Smola et al 2015;Takahashi et al 2016;Watters et al 2016). These apparently contradictory results stimulated us to further investigate the differences between the two types of SHAPE reagents.…”
Section: Resultsmentioning
confidence: 99%
“…Published work has reported in vivo modification of RNA in E. coli cells; however, no cDNA truncation blots were shown (McGinnis et al 2015;Smola et al 2015;Takahashi et al 2016). To address the possibility that our lack of in vivo signal using 1M7 is due to the type of cells used, we repeated the SHAPE experiment in HST08 E. coli cells following precisely the published protocols for cell culture, RNA modification, and RNA extraction (McGinnis et al 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutational profiling analysis is particularly useful for identifying correlations between two positions within a single RNA but has the drawback that mutational profiling analysis requires much deeper sequencing to confidently call a nucleotide single stranded because there may be mutations incorporated during library preparation unrelated to a SHAPE adduct. This method has the potential to become an in vivo probing method by incorporating one of the cell-permeable SHAPE reagents (102,105).…”
Section: In Vitro Genome-wide Methodsmentioning
confidence: 99%